Mangrove Trace Metal Biogeochemistry Response to Global Climate Change - de Lacerda, Luiz Drude; Ward, Raymond D.; Borges, Rebecca; Ferreira, Alexander Cesar (Frontiers in Forests and Global Change, 2022)
This review discusses observed impacts from different climate change-driven pressures on mangrove’s role in modulating trace metal transfer at the land-ocean interface. It contributes to the literature in a global context and shows mangroves as mitigators or providing positive feedback to metal mobilization. Most chalcophile metals2+ accumulate in mangrove soils associated with sulfides while high sedimentation rates avoid their oxidation. Exudation of oxygen by roots fixates Fe, which co-precipitates metals as oxyhydroxides in the rhizosphere. These two biogeochemical processes reduce trace metal availability to plants and their mobility within estuaries. However, climate change-driven pressures alter this geochemical equilibrium. Increasing atmospheric CO2 and temperature, and the intensity and frequency of extreme climatic events, have proved to affect mangrove functioning and cover, but no direct observation on the impact on metal biogeochemistry is presently available, whereas sea level rise and saline intrusion impacts on the fate of metals have already been observed. Sea level rise increases erosion, that dissociates deposited sulfides releasing metals to the water column. Released metals adsorb onto suspended particles and can re-deposit in the estuary or are exported to continental shelf sediments. Saline intrusion may oxidize deeper sediment layers releasing metals to porewaters. Part of the mobilized metals may remain in solution complexed with DOM and have their bioavailability increased, as shown by high bioaccumulation factors and biomagnification and high metal concentrations in the estuarine biota, which results in higher human exposure through fisheries consumption. Since erosion occurs preferentially at the sea border and higher sedimentation at the higher reaches of the estuary, triggering mangroves migration landward, spatial gradients are formed, and shall be taken into consideration when planning mitigation or adaptation strategies. These observations suggest disruption of traditional humans dwelling in mangrove dominated coastlines by increasing contamination of coastal fisheries, often the principal protein source for those groups and an important source of income. Further research into the environmental and socioeconomic impacts of climate change driven alterations to metal biogeochemical processes in mangroves as contaminant levels are expected to increase.